Windchill system architecture landscape within TEWI administrative domain. - Kłosiński, Marcin (Wydawnictwo Politechniki Łódzkiej, 2014)
This paper covers some chosen aspects of Windchill system architecture elements that are crucial from TEWI administration standpoint. Those aspects are above all: Windchill overall architecture landscape, system components and common administrative activities for TEWI platform maintenance.